The effectiveness of entrepreneurial education in spreading and promoting the entrepreneurial culture in the Algerian University An exploratory study of the Entrepreneurial Houses managers’ opinions in some Algerian universities - amal mahawa; farah khaldi (Journal of Excellence for Economics and Management Research, 2021)
The study aims to analyze the impact of entrepreneurial education in spreading the culture and promotion of entrepreneurship in the Algerian University by analyzing the opinions of the managers of the Entrepreneurial House in some Algerian universities, the latter which contributed to spreading the entrepreneurial thought among the students who are about to graduate. The study relies on the questionnaire analyzed by the SPSS statistical program.Finally, the study concludes that business education at the Algerian University is a solid ground for developing youth knowledge that reflects positively on small and medium enterprises developed through personal, administrative and technical skills.